Phonon abundance-stiffness-lifetime transition from the mode of heavy water to its confinement and hydration - Peng, Yuan (2021)
A combination of the spatially- and temporally-resolved phonon spectroscopies has enabled calibration of hydrogen bond transition from the vibration mode of heavy water to the core-shell structured nanodroplets and to the ionic hydration shells of salt solutions in terms of phonon abundance-lifetime-stiffness. It is uncovered that charge injection by salt solvation and skin formation by molecular undercoordination (often called confinement) share the same supersolidity characterized by H–O (D–O as a probe) bond contraction, O:H nonbond elongation, and polarization. Such a process of bond transition stems the solution viscosity, surface stress, and slowing down of the molecular dynamics and diffusivity. The nanodroplet skin reflection further hinders phonon energy dissipation associated with longer D–O phonon lifetime.